Habitat partitioning during character displacement between the sexes. (20th June 2018) - De Lisle, Stephen P.; Paiva, Samuel; Rowe, Locke
Abstract : Ecological differences between the sexes are often interpreted as evidence of within-species ecological character displacement (ECD), a hypothesis with almost no direct tests. Here, we experimentally test two predictions that are direct corollaries of ECD between the sexes, in a salamander. First, we find support for the prediction that each sex has a growth rate advantage in the aquatic microhabitat where it is most commonly found. Second, we test the prediction that selection for ECD in the breeding environment may affect partial migration out of this environment. We found that phenotype-dependent migration resulted in a shift in the phenotypic distribution across treatments, with the highest sexual dimorphism occurring among residents at high founding density, suggesting that migration and ECD can both be driven by competition. Our work illustrates how complex patterns of habitat partitioning evolve during ECD between the sexes and suggest ECD and partial migration can interact to effect both ecological dynamics and evolution of sexual dimorphism.